2021
DOI: 10.1002/lary.29777
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Olfactory Psychophysical Scores and SARS‐CoV‐2 Viral Load in COVID‐19 Patients

Abstract: Objectives/Hypothesis: The aim of this study was to evaluate the correlations between the severity and duration of olfactory dysfunctions (OD), assessed with psychophysical tests, and the viral load on the rhino-pharyngeal swab determined with a direct method, in patients affected by coronavirus disease 2019 .Study design: Prospective cohort study. Methods: Patients underwent psychophysical olfactory assessment with Connecticut Chemosensory Clinical Research Center test and determination of the normalized vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
(169 reference statements)
0
13
1
Order By: Relevance
“…18 Similarly, risk factors for the persistence of OD have not yet been identified. 19-23 Different from any other long-term follow-up study, 5,6,8 female sex had a significant association with persistence of OD.…”
Section: Discussioncontrasting
confidence: 63%
“…18 Similarly, risk factors for the persistence of OD have not yet been identified. 19-23 Different from any other long-term follow-up study, 5,6,8 female sex had a significant association with persistence of OD.…”
Section: Discussioncontrasting
confidence: 63%
“…It has not yet been clarified what the frequency of persistent disturbances is in these groups of individuals, but if the prevalence recorded in cases of primary infection were confirmed, it would mean that this problem may not end with the immunization of the population. Second, the identification of the pathogenesis [54][55][56][57][58][59][60][61] and risk factors [2][3][4][5][6][7][8][9][10][11][12][62][63][64][65][66][67][68] for the development of persistent CD are in its infancy. For this reason, no effective therapies have yet been found for the prevention and treatment of COVID-19 related POD and PGD [69][70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…If this prevalence were so high even in vaccinated subjects, we could still have a high number of subjects who will require assistance for such disabling disorders. The risk factors and causes of persistence of CD in some patients have not yet been identified 16–20 . Early studies found no significant correlation between serum immunoglobulin levels and duration of olfactory disfunction 21,22 .…”
Section: Discussionmentioning
confidence: 99%